Cost-effectiveness analysis of brolucizumab versus aflibercept for the treatment of neovascular age-related macular degeneration (nAMD) in Italy - Nicola Ferrante; Daniela Ritrovato; Rossella Bitonti; Gianluca Furneri (BMC, 2022)
Abstract Background Age-related macular degeneration (AMD) is a common and chronic eye condition characterized by the presence of progressive degenerative abnormalities in the central retina (macula). Notably, neovascular, or wet, AMD (nAMD) occurs when new, abnormal blood vessels grow under the macula causing scarring of the macula itself and resulting in a loss of central vision, visual distortion, and an impaired capacity of perceiving colour contrast and intensity. Brolucizumab, a new generation anti-vascular endothelial growth factor (anti-VEGF) monoclonal antibody, was approved by the European Medicines Agency for the treatment of nAMD. The aim of this analysis is to evaluate the cost-effectiveness profile of brolucizumab, compared to the main therapeutic alternative available (aflibercept), for the treatment of nAMD. Methods The simulation of costs and outcomes was carried out using a Markov model over a time horizon of 15 years. In base-case, treatment effectiveness inputs for brolucizumab and aflibercept were extracted from the HAWK and HARRIER studies and from a network meta-analysis. The Italian National Healthcare Service (NHS) perspective was considered, therefore only healthcare direct costs (treatment acquisition, administration, adverse events, disease monitoring) were analysed. In the alternative scenarios, the societal perspective and a prolonged time horizon were considered. Model robustness was tested through sensitivity analyses. Results In the base-case analysis, brolucizumab was dominant over aflibercept (+ 0.11 years QALY gained and -€15,679 costs). Both one-way deterministic and probabilistic sensitivity analyses confirmed the robustness and reliability of base-case results. The results of the probabilistic sensitivity analysis showed that when the willingness to pay is equal to €50,000 per QALY gained, brolucizumab would be dominant in 84% of simulations and in the remaining simulations brolucizumab would be cost-effective compared to aflibercept. Results of the alternative scenarios and sensitivity analyses confirmed the results of base-case. Conclusion The cost-utility analysis shows that brolucizumab is dominant over aflibercept. Treatment with brolucizumab reduces the economic impact of nAMD and determined a slight increase of quality-adjusted survival. This analysis gives a high level of confidence that the treatment with brolucizumab would reduce the burden of intravitreal injections, compared to aflibercept, a relevant therapeutic alternative in Italy.